Speech and Language Pathology and Communication´s rights - Teira Serrano, Celia (Revista de Investigación en Logopedia, 2021)
Are we aware that communication is a human right? Are we aware we are violating human rights when we do not consider Augmentative and Alternative Communication systems in our practice? Have we ever thought about the rights of the people we work with? Not having to think about your own rights about accessibility, capacities…, usually means you have some kind of privileges related to a supposed normality that affects most of the population. Speech and Language Pathology should be framed in a human rights perspective. It should be mandatory to have knowledge of concepts such as the ‘right to communicate’, its origin and present legal status, as well as ‘accessibility’, a consequence of the barriers that right is facing. This article supports this knowledge about communication as a Human Right should be incorporated in our formal education as future professionals in the aim of Speech-Language Pathology.
Keywords: Accessibility; Communication; Disability; Human rights; Speech and Language Pathology